FACTORS INFLUENCING INDONESIAN ACCOUNTING STUDENTS' PERCEPTION OF SAFE HAVEN INVESTMENTS - Irianto, Okto; Manuhutu, Fenty Yoseph; Ada, Kadek Bramdhika; Adiatma, Tini; Rachman, Adi Maulana (Jurnal Aplikasi Akuntansi, 2025)
This study aims to identify and analyze the factors that influence the perception of Accounting students in Indonesia towards safe haven investments in the context of global economic uncertainty due to the US-China trade war. Continued economic uncertainty encourages investors to seek hedging instruments, but the understanding of the younger generation as prospective financial practitioners towards safe havens is still limited. This explanatory quantitative study uses primary data from 168 accounting students through a structured questionnaire. Data analysis uses Structural Equation Modeling with Partial Least Squares (SEM-PLS) to test the effect of financial knowledge level, investment experience, risk tolerance, and exposure to market information on safe haven perceptions. The results show that the level of financial knowledge has the most significant positive effect on safe haven perceptions, followed by investment experience and exposure to market information, which also have a positive impact. Conversely, risk tolerance has a significant adverse impact on safe haven perceptions. The research model explains 54.7% of the variance in safe haven perceptions with good predictive relevance. These findings imply the need to strengthen financial literacy and experiential learning in the accounting curriculum to prepare graduates with a comprehensive understanding of investment risk management in an era of global economic uncertainty.